Sosialisasi Pengembangan Usaha Dan Pencatatan Keuangan UMKM - Erni Hernawati; Anita Anita; Lisa Amru (Pusat Riset dan Inovasi Nasional, 2024)
Financial records are important in managing the business of an MSME. Good and accurate financial records will help MSMEs to know the state of their business and can help MSMEs develop their business. The implementation of Community Service aims to provide socialization on business development and financial records for ayam penyet sambal ijo Ibu Any business in Pamulang. Ayam penyet sambal ijo Ibu Any business has a great potential to develop, but this is not accompanied by good financial records. The method used in dedication to this society is socialization about simple financial records and how to develop a business. The result of this dedication is that ayam penyet sambal ijo Ibu Any business has simple financial records and knows how to develop the business, so that Ms. Any's business can thrive.